HUBUNGAN PENILAIAN KINERJA DAN PENGEMBANGAN KARIER DENGAN MOTIVASI KERJA PARA KARYAWAN - Fathudin Ali (Universitas Nurul Jadid, 2021)
The purpose of this study is to determine the extent of the relationship between performance appraisal and career development with the work motivation of employees at the Al-Ikhlas Mosque Foundation (YMAI). The research used an experimental approach and inferential statistical analysis. The research population consisted of several YMAI employees randomly selected from each work unit, namely SD units, SMP units, KB/TK units, and Secretariat units. The result is Chi-Square = 0.05, df = n-1 95% confidence level. So that employee assessment positively affects employee performance and can be accepted. This is evident from the results of the t-test calculation; the t-test results state that the t-value for the employee development variable is 5.534, with a probability of 0.000. Using a significant level of 5%, the probability value is less than 0.05. This shows that H2 is accepted and H0 is rejected, so it can be concluded that the employee development variable has a positive and significant effect on employee performance.